2018
DOI: 10.1002/macp.201700478
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of Epoxides and CO2 by Cobalt(II) Oxaporphyrins with Mechanistic Explorations on Poly(Propylene Carbonate) Formation

Abstract: Two cobalt(II) oxaporphyrins (OTPPCoCl and OTPPCoSbF6) are synthesized in this work and are characterized, including by X‐ray crystallography. Both complexes are tested as catalysts in the copolymerization of propylene oxide (PO)/cyclohexene oxide (CHO) and CO2. Polycarbonate is obtained in CHO/CO2 copolymerization with OTPPCoCl as a catalyst, whereas in the case of PO, cyclic carbonate (CC) is majorly formed. An anion exchange from Cl− to SbF6 − of the cobalt(II) oxaporphyrin leads to a drastic change in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…S61 †) and the data are interpreted with the values reported in the literature. 43 The carbon atom of the -CvO moiety in polymeric carbonates exhibits 13 C NMR signals at 154.0 ppm (syndiotactic) and 153.3 ppm (isotactic). 100a,b Our findings (Fig.…”
Section: Catalytic Activity Towards Co 2 Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…S61 †) and the data are interpreted with the values reported in the literature. 43 The carbon atom of the -CvO moiety in polymeric carbonates exhibits 13 C NMR signals at 154.0 ppm (syndiotactic) and 153.3 ppm (isotactic). 100a,b Our findings (Fig.…”
Section: Catalytic Activity Towards Co 2 Fixationmentioning
confidence: 99%
“…Among them, the most eminent and economically reliable method, especially in terms of maximum atom economy, is CO 2 fixation to epoxides. 24–27 A number of metal-complex catalysts such as zinc, 28–32 cobalt, 33–65 b chromium, 66–69 magnesium, 70–72 iron, 73–75 c nickel, 76–78 and rare-earth metal 79–81 based catalysts have been developed for CO 2 fixation. Among these, cobalt salen complexes are well known for their enhanced activity and selectivity towards CO 2 fixation.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of CO 2 as the C1 source for the production of valuable chemicals is attracting increasing interest because CO 2 is inexpensive, nontoxic, and abundant. One promising method is the copolymerization of CO 2 and epoxides, which produces polycarbonates that have found many applications in packaging, agricultural, and biomedical industries. A number of catalysts have been developed for copolymerization, including complexes of zinc, cobalt, chromium, magnesium, iron, nickel, and rare-earth metals. Among these examples, cobalt salen complexes have been reported to show good activity and selectivity (Scheme , left). Coates et al reported the first Co­(III) salen complex, which gave >99% selectivity to poly­(propylene carbonate) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for the selective and efficient synthesis of polycarbonates (PCs) from the copolymerization of CO 2 and epoxides, many Lewis acid catalysts such as organometallic complexes usually used in combination with a nucleophile have been developed. In particular, the important characteristics of metal-based catalysts (zinc [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], aluminum [38,39], chromium [40][41][42][43], cobalt [44][45][46][47], magnesium [48,49], iron [19,[50][51][52][53][54], titanium [55,56], copper [57], ytterbium [58], . .…”
Section: Introductionmentioning
confidence: 99%